2022
DOI: 10.3389/fphar.2022.943638
|View full text |Cite
|
Sign up to set email alerts
|

Dracaena cochinchinensis stemwood extracts inhibit amyloid-β fibril formation and promote neuronal cell differentiation

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by the deposition of amyloid plaques in the brain. The prevention of amyloid-β (Aβ)-induced neuronal toxicity is considered a major target for drug development for AD treatment. Dracaena cochinchinensis (Lour.) S.C. Chen, a Thai folk medicine named “Chan-Daeng,” is a member of the Asparagaceae family. The stemwood of D. cochinchinensis has been traditionally used for its antipyretic, pain relief, and anti-inflammatory effects. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Previous findings have demonstrated that the ethanol extract of DCS exhibited a higher yield and greater pharmacological activities, as compared to the water extract ( Ospondpant et al, 2022 ; Ospondpant et al, 2023 ). To develop a promising BHP of DCS and AEF, various ratios of DCS and AEF ethanol extracts were conducted to determine the optimal level of synergism.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Previous findings have demonstrated that the ethanol extract of DCS exhibited a higher yield and greater pharmacological activities, as compared to the water extract ( Ospondpant et al, 2022 ; Ospondpant et al, 2023 ). To develop a promising BHP of DCS and AEF, various ratios of DCS and AEF ethanol extracts were conducted to determine the optimal level of synergism.…”
Section: Resultsmentioning
confidence: 89%
“…To investigate potential synergistic effects, the aqueous extracts from BHP of two botanical drugs were tested at a fixed combination of 1:1 w/w ratio. Previous studies have reported that DCS alone could promote neuronal differentiation and inhibit Aβ 1-42 aggregation ( Ospondpant et al, 2022 ). Therefore, DCS was selected as the main component to determine potential activity in BHP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The differentiated PC12 cells were cultured in DMEM with high glucose (Gibco) and 10% FBS in a 5% CO 2 incubator at 37°C. Aβ 1−42 was dissolved in PBS at 2 mM and incubated for 5 days at 37°C to aggregate into fibrils before use (Ospondpant et al, 2022). To assess the cytotoxicity of compounds 1-3, PC12 cells were treated with 0.001, 0.01 and 0.1 μM of indicated compounds for 36 h. To investigate the neuroprotective effect and mechanism of compounds 1-3, PC-12 cells were pretreated with indicated compounds (0.001, 0.01, and 0.1 μM) or memantine hydrochloride (0.1 μM) as a positive control for 12 h, and co-incubated with 20 μM Aβ 1−42 for another 24 h. Blank control group contained untreated cells.…”
Section: Extraction and Isolationmentioning
confidence: 99%